Meridional changes in water mass distributions off NW Africa during November 2007/2008 - Pastor, Maria V.; Peña-Izquierdo, Jesús; Pelegrí, Josep Lluís; Marrero-Díaz, Ángeles (Universidad Autónoma de Baja California, 2012)
Special issue on Descriptive Oceanography with Tracers in Coastal and Deep Oceans.-- 22 pages, 9 figures, 3 tables [En] An optimum multiparameter analysis was applied to a data set for the eastern boundary of the North Atlantic subtropical gyre, gathered during November of two consecutive years and spanning from 16 to 36° N. This data set covers over 20° of latitude with good meridional and zonal resolution over the whole coastal transition zone. The contribution from six water types in the depth range between 100 and 2000 m is solved. In the 100 to 700 m depth range the central waters of southern and northern origin meet abruptly at the Cape Verde Frontal Zone. This front traditionally has been reported to stretch from Cape Blanc, at about 21.5° N, to the Cape Verde Islands, but in our case it penetrates as far as 24° N over the continental slope. South of 21° N latitude we actually find a less saline and more oxygenated variety of South Atlantic Central Water, which we ascribe to less diluted equatorial waters. In the 700 to 1500 m depth range the dominant water type is a diluted form of Antarctic Intermediate Water (AAIW), whose influence smoothly disappears north of the Canary Islands as it is replaced by Mediterranean Water (MW); at latitudes where both water masses coexist, we observe MW offshore while AAIW is found near-shore. North Atlantic Deep Water is the dominating water type below about 1300/1700 m depth south/north of the Canary Islands; this abrupt change in depth suggests the existence of different paths for the deep waters reaching both sides of the archipelago [Es] Se aplicó un análisis multiparamétrico óptimo a un set de datos en el margen oriental del giro subtropical del Atlántico Norte, recogido en noviembre de dos años consecutivos y que se extiende entre las latitudes 16 y 36º N. El set de datos cubre unos 20º de latitud y tiene una buena resolución latitudinal y zonal en toda la región de transición costera. La contribución de seis tipos de agua es resuelta en el intervalo de ...